A Treasury of Illustrated Children's Books / Early Nineteenth-Century Classics from the Osborne Collection - Vries Leonard De (Allyn And Bacon, 1989)
Introduction, The Comic Adventures of Old Mother Hubbard and Her Dog, The Butterfly's Birth-day, Death and Burial of Cock Robin, My Daughter and My Pony, The Courtship and Marriage of Jerry and Kitty, The Cries of London as They Are Daily Practiced, An Alphabetical Arrangement of Animals for Little Naturalists, The Good Child's Book of Stops: Or Punctuation in Verse, The History of Sixteen Wonderful Old Women, Dame Wiggins of Lee and Her Seven Wonderful Cats, Cinderella and or The Little Glass Slipper, The Antropologist's Anthology, Bibliography.